The Chinese Company's Entry into International Markets As A Growth Point for The Business - Peng Zhang; Maxim Chernyaev (Communications of International Proceedings, 2021)
The article discusses the main strategies for entering foreign markets. The authors considered not only the main forms of entering international markets, but also analyzed the key motives, stages, advantages and problems of each of the described methods, and also specifically analyze this situation using the example of Chinese. In the context of globalization and the situation of the modern economy, the relevance of this article is determined by the need to identify and evaluate the most effective forms of entry of companies into foreign markets in the current conditions of the international business environment. Despite the unprecedented challenges and uncertainties facing the global economy in the COVID-19 environment, Chinese companies will continue to look for growth opportunities in international markets. The COVID-19 pandemic has disrupted business operations. The formation of new innovation systems, supported by foreign direct investment and the policies of the Government of the People's Republic of China, both in high-tech manufacturing and in research and development, has contributed to structural changes and provided opportunities for mutual knowledge exchange between national and foreign companies. This was proved by the example of the company chosen in this article Jinhua JOBO Technology Co.
Keywords: Globalization; International Markets; Growth; Business.